Soil-dwelling Bacillus velezensis SS-38.4 efficiently colonizes sugar beet phyllosphere and controls phytopathogenic Pseudomonas syringae - Iva Rosić; Ivan Nikolić; Marina Anteljević; Snežana Đorđević; Tanja Berić; Slaviša Stanković; Olja Medić (Phytopathology Research)
Abstract Beneficial plant-associated Bacillus species are widely explored and appreciated as eco- and environmental-friendly plant growth-promoting and biocontrol agents but often fall short of achieving the desired effect in plants. In terms of crop protection, Bacillus spp. have been repeatedly scrutinized for their secondary metabolites involved in direct antimicrobial activity towards phytopathogens or inducing systemic resistance in host plants. However, integral aspects of successful implementation of a biocontrol agent, the pronounced colonization capacity and adaptability to variations in abiotic and biotic parameters of a new environment, have been underestimated and underexplored. Here, we demonstrate that the soil-dwelling Bacillus velezensis SS-38.4 can successfully colonize the sugar beet phyllosphere, establish a stable and persistent population owing to its superior motility, ability of surfactin and biofilm production, supported by findings of genome analysis, achieving efficient suppression of the bacterial leaf spot disease. In the phyllosphere, B. velezensis SS-38.4 appears to employ an offensive strategy initiated by a swift invasion of a nonnative niche, reinforced by iron depletion and a wide arsenal of antimicrobials directed towards the phytopathogen. By displaying competitive behavior beyond its original ecological niche, B. velezensis SS-38.4 has exhibited its resilience and versatility in a challenging environment, reflecting its suitability for implementation as a biocontrol agent for efficient and comprehensive crop protection.